RESTOCKING OF WINDU SEEDS (Penaeus monodon) RESULTS OF THE ACULTURE PRODI'S OWN FISHING IN THE LANGSA CITY FISHING AREA: RESTOCKING BENIH UDANG WINDU (Penaeus monodon) HASIL PEMBENIHAN MANDIRI PRODI AKUAKULTUR PADA KAWASAN PERAIRAN KOTA LANGSA - Achmad Zacky Shodri; Suri Purnama Febri; Cici Maulida; Muhammad Hanif; Romaya Sefti Sinaga; Rizky Akbar Pratama; Alhamda; Dary Akbar Saputra; Fitria Ningsih; Rizka Musfirah; Siti Balqies Indra; Fiddini Alham (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
Tiger prawns (Penaeus monodon) are native Indonesian shrimp with high economic value. Tiger prawns or black tiger prawns are the largest component of Indonesian fishery products that have contributed 34.5 percent to the export market. In maintaining its availability in the waters, tiger prawn stock management activities must be carried out so that the chances of a decline in its population in nature are getting smaller. Tiger prawn cultivation activities are still very little carried out, while uncontrolled fishing activities will affect the reduction of tiger prawn stocks in nature. One effort that can be made to maintain the balance of tiger prawn stocks is through restocking activities. Restocking is an effort to increase the stock of tiger prawns caught that are spread in public waters. The purpose of tiger prawn restocking activities, in addition to increasing the stock of tiger prawns in nature, is to restore the role and function of balanced public waters. The method of implementing tiger prawn restocking used in PKM activities is through several stages such as providing tiger prawn seeds which are carried out through independent seeding, the extension stage, and the restocking implementation stage. The outputs produced from the PKM activities that have been implemented are national electronic mass media publications, waspada.id newspapers and promotions of the Aquaculture Study Program, Samudra University, in Langsa City; able to produce intellectual wealth by achieving species protection so that there is no drastic decline in numbers, especially in the waters of Langsa City